Achieving SDG-16 in State Owned Enterprise by Implementation of ISO 37001: Anti-Bribery Management - Nur'Asih Budhi Dharma Putri; Ampuan Situmeang; Triana Dewi Seroja (Journal of Law and Policy Transformation, 2024)
In 2021, SOEs Minister Erick Thohir launched the AKHLAK program to address SOEs problems including corruption cases. Indonesia as a member of the UN has an agenda to achieve, which is Sustainable Development Goals (SDGs). The high number of corruption cases in SOEs slows down the achievement of SDGs, especially no. 16 "Peace, Justice and Strong Institutions". The research method uses normative juridical with secondary data sources as the main data and also supported by primary data. The results showed that the implementation of ISO 37001 Anti-Bribery Management System in SOEs can prevent bribery and is normally implemented thoroughly in about 4-6 months. The obstacles to implementing ISO 37001 in SOEs are influenced by the commitment of the leadership of SOE institutions.